Between Freedom and Imprisonment. The Shanghai Ghetto from the Perspective of the Bulgarian Writer Angel Wagenstein - Kuczyńska, Marzanna (Poznańskie Studia Slawistyczne, 2023)
Angel Wagenstein’s novel Farewell, Shanghai is this article’s focal point. The attention focuses on the literary picture of the Shanghai ghetto (Hongkew district) during the Second World War. Wagenstein shows the ghetto as symbol of the end of the Jews’s eternal wandering, where they found autonomy from other nations, and reunification based on sufferings and religion. Before them there stands the long-awaited promised land, where they themselves will govern themselves.